CRITICAL ANALYSIS OF THE FORMAL PASRAMAN CURRICULUM - Kusuma Dewi, Ni Wayan Sri Prabawati; I Wayan Lasmawan; I Gusti Putu Suharta (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Formal Pasraman is a form of Hindu Religious education, which consists of Primary WidyaPasraman, Adi Widya Pasraman, Madyama Widya Pasraman, Main Widya Pasraman and MahaWidya Pasraman. The Pasraman curriculum is regulated in articles 8 and 9, which state explicitlythat the curriculum consists of the Hindu religious curriculum and the general educationcurriculum. The formal pasraman curriculum must be able to meet the competencies of 21stcentury graduates. The relevance of the formal pasraman structure as well as the rationalization ofthe curriculum structure that has been stipulated in PMA No. 10 of 2020 is very important to study.For this reason, this research was conducted using a qualitative descriptive research method, in acritical study with a literature study approach. The results of the research were found as follows; 1.The relevance of the pasraman curriculum structure; analyzed from the nine national educationstandards of education, taking into account aspects of flexibility, the basic logic of the curriculum,dimensions and supporting aspects, it is concluded that the formal pasraman, especially in terms ofcurriculum structure, is not yet relevant to the needs of the 21st century. others, as well as theorientation of the analysis of the planning context, process and results of formal pasraman content,to create Hindu-based superior quality schools.